Impact of Clazosentan on Vasospasm Reduction and Functional Recovery after Aneurysmal Subarachnoid Hemorrhage - Sosho KAJIWARA; Takayuki KAWANO; Yu HASEGAWA; Yukihiko NAKAMURA; Kiyohiko SAKATA; Jin KIKUCHI; Masaru HIROHATA; Motohiro MORIOKA (Neurologia Medico-Chirurgica)
In every hospital in Japan, until 2022, the primary treatment for preventing delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH) involved a combination of ozagrel sodium (Oz), fasudil hydrochloride (Fs), cilostazol, and statins. However, with the approval of clazosentan in January 2022, it has been used as a first-choice drug more frequently. Despite this shift, limited evidence exists regarding the use of clazosentan as the first choice for DCI prevention. In this study, we analyzed the efficacy and outcomes of these two treatments in aSAH patients. Patients treated with Oz+Fs were enrolled between January 2014 and March 2022. In April 2022, clazosentan was prescribed to prevent DCI. Clinical data were collected, and propensity-score matching was conducted based on the clazosentan group. The primary endpoint was the functional outcome at discharge and 6-12 months after admission; the secondary endpoints were the incidence of cerebral vasospasm (CV) and DCI. In this study, 221 patients were included, and 27 were selected from both groups after matching. The incidence of CV was significantly lower in the clazosentan group (11.1% vs. 55.6%, p<0.01), and the incidence of DCI tended to be lower in the clazosentan group (3.7% vs. 25.9%, p=0.05). No significant difference was observed in the primary endpoint of functional outcome at discharge; however, a significant improvement in functional outcome was observed in the clazosentan group at 6 months (96.3% vs. 70.4%, p<0.05). Clazosentan significantly reduced the incidence of CV and improved functional outcomes in patients with aSAH compared to Oz+Fs.